On the Origin and Tasks of Czechoslovak Foreign Policy and Methods and the Character of Czechoslovak Diplomacy (Czech Journal of International Relations, 2024)
O původu a úkolech československé zahraniční politiky a metodách a charakteru československé diplomacie